The interplay of HRM practices, organizational climate, and employee outcomes on organizational outcomes in accommodation facilities in the Central Philippines - Ryan Tayco (Journal of Rural Tourism, 2025)
Purpose – This study investigates how HRM practices, organizational climate, and employee outcomes affect organizational outcomes in accommodation facilities in Central Philippines.Methodology/Design/Approach – Using a correlational design, the study examined the relationships among HRM practices, organizational climate, employee outcomes, and organizational performance. Data were collected via survey from 805 respondents (123 supervisors/managers and 682 staff) across various registered accommodation facilities, including hotels, resorts, inns, pension, and lodging houses. The findings are more applicable to larger operations like hotels and resorts.Findings – Results show a significant relationship between HRM practices, organizational climate, and employee outcomes with organizational performance. Facilities with favorable HRM practices, positive organizational climate, and strong employee outcomes tend to have better organizational performance.Originality/Value – This study uniquely explores the combined influence of HRM practices, organizational climate, and employee outcomes on hotel performance in Central Philippines, offering localized insights for strategic hospitality management and regional business sustainability.